Utility of respiratory viral testing in the risk stratification of young febrile infants presenting to emergency care settings: a protocol for systematic review and meta-analysis - Thomas Waterfield; Hannah Mitchell; Etimbuk Umana; Jordan Evans; Lisa McFetridge; Clare Mills; Hannah Norman-Bruce; Jennie Roe (BMJ Publishing Group, 2024)
Introduction Febrile infants under 3 months of age are at risk of invasive bacterial infection (IBI). It is currently unclear if testing for respiratory viruses may have a role in IBI risk stratification. If found to be associated with the likelihood of IBI, respiratory viral point-of-care testing may improve patient and caregiver experience, reduce costs and enhance antimicrobial stewardship.Methods and analysis This is a study protocol for a systematic review and meta-analysis that aims to answer the following question: In young febrile infants presenting to emergency care settings does a positive respiratory viral test for RSV, Influenza or SARS-CoV2 (relative to a negative test) add value to current risk stratification pathways for the exclusion of invasive bacterial infection, subsequently enabling safe de-escalation of investigation and treatment?A search strategy will include MEDLINE, EMBASE, Web of Science, The Cochrane Library and grey literature. Abstracts and then full texts will be independently screened for selection. Data extraction and quality assessment will be completed by two independent authors.The primary objective is to analyse the ability of a positive respiratory viral test to identify the overall risk of IBI. The secondary objective is to perform a subgroup analysis to investigate how the risk stratification alters based on other variables including virus type, patient characteristics and the presence of an identified source of fever.Bivariate random-effects meta-analysis will be undertaken. Diagnostic odds ratios (OR), sensitivity, specificity and positive and negative likelihood ratios will be calculated. The degree of heterogeneity and publication bias will be investigated and presented.Ethics and dissemination Ethical approval is not required. We will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to disseminate the study results through publication and conference presentations.PROSPERO registration number This protocol is registered in PROSPERO-ID number: CRD42023433716.